Validation of the Reliability of the Porous Structure Parameters for Activated Carbons as Evaluated on the Basis of Adsorption Isotherms from the Gaseous Phase - Bogdan J. Trznadel; Stefan Zietek; Andrzej Światkowski (Adsorption Science & Technology)
Adsorption/desorption isotherms from the gaseous phase (benzene vapour, nitrogen) have been determined consecutively a number of times on the same activated carbon sample. The porous structure parameters were evaluated on the basis of the experimental data using the Dubinin-Radushkevich, Dubinin-Astakhov, Finger-Büllow, Dubinin-Stoeckli and Horvath-Kawazoe equations for the calculations. Analyses of the mean values and relative errors of particular structural parameters were made as well as comparisons of the stability of the adsorption models used. It was found that the reliability of the results obtained was better for the benzene vapour adsorption isotherms determined by a gravimetric method than for those determined by a volumetric method using nitrogen as the adsorbate.